Contribution of T cell subset analysis in induced sputum in diagnosing ocular sarcoidosis - Meshi, A.; Neudorfer, M.; Fireman, E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Objective: The aim of this study was to establish a correlation between the diagnosis of ocular sarcoidosis and the presence of an elevated CD4/CD8 ratio in the induced sputum(IS) of patients with uveitis and no other systemic symptoms. Methods: This retrospective chart review study included all newly diagnosed uveitis patients treated between 1998-2006. IS examinations and determination of angiotensin-converting enzyme (ACE) levels were carried out. A CD4/CD8 ratio >2.5 and an ACE level >145 μl/ml/min were considered abnormal.The etiology of uveitis was retrieved from the medical records. Results: Twenty males and 26 females (mean age 47±16.1 years) were enrolled. The CD4/CD8 ratio was elevated in 26 (56.5%) patients, and five (10.9%) were diagnosed as having sarcoidosis by the end of follow-up.The sensitivity and specificity of the T lymphocytes CD4/CD8 ratio in diagnosing sarcoidosis were 100% and 48.8%, respectively. CD4/CD8 ratios were not significantly different between the sarcoid and non-sarcoid groups (p>0.05), but the former tended to have higher levels (p=0.0991). The mean ACE level of the sarcoid patients was significantly higher than that of the non-sarcoid patients (p